Immunoexpression of progesterone receptor, epithelial growth factor receptor and galectin-3 in uterine smooth muscle tumors - Soltan, Mervat M.; Albasry, Abdelkader Mohammed; Eldosouky, Maha K.; Abdelhamid, Hanan S. (Cellular and Molecular Biology, 2018)
Uterine smooth muscle tumors constitute a spectrum of neoplasms. Diagnosis of leiomyomas (LMs) is usually straight forwards; however, atypical leiomyomas (ALMs) and smooth muscle tumors of uncertain malignant potential (STUMPs) have overlapping features and need to be distinguished from leiomyosarcoma. To evaluate progesterone receptor (PR), epithelial growth factor receptor (EGF-R), and galectin-3 expression in LMs, ALMs, STUMPs, and leiomyosarcomas and to assess their possible role in differentiating those tumors. Immunoexpression of EGF-R, PR, and galectin-3 were studied in 44 cases of uterine smooth muscle tumors through retrospective study. Studied cases included 20 LM, 9 ALM, 5 STUMP, and 10 leiomyosarcomas. A semiquantitative score was used to evaluate immunohistochemical staining. EGF-R overexpression was detected in leiomyosarcomas while a lack of or reduced EGF-R expression was observed in the nonsarcomatous group (LMs, ALMs, and STUMPs) with a highly significant difference. On the contrary, there was weak or negative PR staining in leiomyosarcomas compared to intense PR expression in the nonsarcomatous group with a highly significant difference. Meanwhile, galectin-3 was downregulated in leiomyosarcomas compared to the nonsarcomatous group with a significant difference. Correlation analysis revealed negative correlation between EGF-R and PR expression with significant statistical results while correlation of galectin-3 with EGF-R and PR showed insignificant statistical results. Immunoexpression of EGF-R, PR, and galectin-3 could help differentiate challenging cases of uterine smooth muscle tumors. Further studies are recommended to investigate interactions between EGF-R, PR, and galectin-3 and to plan new therapeutic strategies.